2000
DOI: 10.1074/jbc.275.15.11327
|View full text |Cite
|
Sign up to set email alerts
|

Wild Type and Mutant p53 Differentially Regulate the Gene Expression of Human Collagenase-3 (hMMP-13)

Abstract: Chem. 274, 11535-11540). Here, we report that cotransfection of fibroblast-like synoviocytes with p53 expression and hMMP13CAT reporter plasmids revealed that (i) hMMP13, another member of the human MMP family, was down-regulated by wild type p53, whereas all six of the p53 mutants tested lost the wild type p53 repressor activity in fibroblast-like synoviocytes; (ii) this repression of hMMP-13 gene expression by wild type p53 could be reversed by overexpression of p53 mutants p53-143A, p53-248W, p53-273H, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 44 publications
5
50
0
1
Order By: Relevance
“…2 Additionally, simultaneous activation/stabilization of p53 and increase of the proteolytic activity are demonstrated here. Together, these results support our assumption of the possible implication of these transcription factors in S100A4-mediated proteinase activation, which is in good agreement with the data on their tight implication in the transcriptional regulation of MMPs (47)(48)(49).…”
Section: S100a4(mts1) In Tumor-stroma Interactionsupporting
confidence: 81%
“…2 Additionally, simultaneous activation/stabilization of p53 and increase of the proteolytic activity are demonstrated here. Together, these results support our assumption of the possible implication of these transcription factors in S100A4-mediated proteinase activation, which is in good agreement with the data on their tight implication in the transcriptional regulation of MMPs (47)(48)(49).…”
Section: S100a4(mts1) In Tumor-stroma Interactionsupporting
confidence: 81%
“…For example, the promoter of the gene encoding the insulin-like growth factor I receptor is repressed by wild-type p53 but stimulated by certain tumour-derived p53 mutants (Werner et al, 1996). Similar observations have been reported for the gene encoding matrix metalloproteinase-13 (Sun et al, 2000).…”
Section: Discussionsupporting
confidence: 68%
“…It can bind to DNA in a sequence-speci®c fashion and stimulate expression of proximal genes (Bargonetti et al, 1991;Farmer et al, 1992;Kern et al, 1991;. As well as activating genes with p53-binding sites, p53 is also able to repress promoters that lack its response element (Cairns and White, 1998;Chesnokov et al, 1996;Crook et al, 1994;Farmer et al, 1996;Ginsberg et al, 1991;Horikoshi et al, 1995;Kley et al, 1992;Mack et al, 1993;Mercer et al, 1991;Ragimov et al, 1993;Santhanam et al, 1991;Seto et al, 1992;Subler et al, 1992;Sun et al, 2000;Venkatachalam et al, 1998;Werner et al, 1996;Yu et al, 1999;Zhao et al, 2000). Although such repression occurs in the absence of a DNA site that is bound directly by p53, it is nevertheless highly speci®c; microarray analysis of *6000 genes showed that only 0.9% were inhibited by p53, whilst 1.8% were induced (Zhao et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggested that secreted p53 would be digested not only by serine protease but also by other kinds of proteases, such as MMP (Figure 4d). As p53 suppresses MMPs at the transcription level (Sun et al, 2000), secreted p53 might be easily digested by elevated MMPs. However, more details can be revealed by further investigation.…”
Section: Resultsmentioning
confidence: 99%